Internationalizing Research in Saudi Arabia: Purchasing Questionable Privilege - Ahmed, Manail Anis (International Higher Education, 2014)
Universities in Saudi Arabia have been taking urgent measures to boost research production in order to be featured in global university rankings. In addition to the many sincere efforts being made to develop a national research enterprise and culture, one of the more dubious practices in this regard is the remote, part-time employment of international highly-cited researchers to publish with a second (Saudi) institutional affiliation. This practice privileges the purchasing of internationally-produced research while ignoring a substantial amount of scholarly output produced within the country in Arabic. The Kingdom could benefit far more from diverting resources instead to supporting research produced locally: by providing rigorous training in international research methods, sponsoring the translation of Arabic research output into English, and in the process educating Saudi researchers about the importance of peer review, academic influence through citation, and ultimately the production of high quality research to an international standard.